2007
DOI: 10.1007/s00198-007-0384-2
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the jaw induced by orally administered bisphosphonates: incidence, clinical features, predisposing factors and treatment outcome

Abstract: ONJ is a rare devastating side effect of oral bisphosphonates associated with patient morbidity and high financial burden. Clinicians must be aware of this entity and inform patients of the risks of dental surgery. The synergistic effect of smoking in the pathogenesis of ONJ should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
158
1
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(176 citation statements)
references
References 25 publications
8
158
1
8
Order By: Relevance
“…Less uniform is the percentage of BRONJ among non-cancer, osteoporotic patients within whole samples also comprising cancer patients: in a multi-center study, a BRONJ frequency of 7.1% in patients treated with oral BP therapy [41] was reported; a frequency of 8.9% of BRONJ after per os BP administration was observed in two Israeli medical centers; and, of all the BRONJ patients in other case series reported in the literature, the percentage of orally-administered bisphosphonate-induced ONJ ranges from 2.5% to 27.3% [58]. In the absence of reliable statistics indicating the number of patients exposed to BPs, it is still not easy to establish the real risk of developing BRONJ for non-cancer patients, also due to the large number of supposed and still unascertained risk factors.…”
Section: European Journal Of Internal Medicine 24 (2013) 784-790mentioning
confidence: 99%
“…Less uniform is the percentage of BRONJ among non-cancer, osteoporotic patients within whole samples also comprising cancer patients: in a multi-center study, a BRONJ frequency of 7.1% in patients treated with oral BP therapy [41] was reported; a frequency of 8.9% of BRONJ after per os BP administration was observed in two Israeli medical centers; and, of all the BRONJ patients in other case series reported in the literature, the percentage of orally-administered bisphosphonate-induced ONJ ranges from 2.5% to 27.3% [58]. In the absence of reliable statistics indicating the number of patients exposed to BPs, it is still not easy to establish the real risk of developing BRONJ for non-cancer patients, also due to the large number of supposed and still unascertained risk factors.…”
Section: European Journal Of Internal Medicine 24 (2013) 784-790mentioning
confidence: 99%
“…11 The dentist must educate the patient preparing to undergo any chemotherapy regimen about the possible dental side effects of BP and take the necessary preventive measures to keep potential side effects to a minimum. 12 The role of hyperbaric oxygen therapy is still unclear but some benefits of this treatment have recently been described in association with discontinuation of BP therapy and conventional therapy (medical or/and surgical). 13 Surgical treatment, in accordance to the American Association of Oral and Maxillofacial Surgeons (AAOMS) Position Paper, is reserved to patients affected by Stage III of BRONJ even if in the last version a superficial debridement is indicated to relieve soft tissue irritation also in the Stage II (lesions being unresponsive to antibiotic treatment).…”
Section: Discussionmentioning
confidence: 99%
“…As ONJ is now a well-known adverse effect of intravenous biphosphonates, one can be falsely reassuring about the safety of oral biphosphonates. According to Yarom et al, of all the ONJ patients in case series reported in the literature, the relative proportion of orally administrated biphosphonate-induced ONJ ranges from 2.5 to 27.3% [25]. In most cases, alendronate, an aminobiphosphonate, was the oral biphosphonate mentioned because it is the most widely used oral biphosphonate.…”
Section: Discussionmentioning
confidence: 99%